57.8k views
4 votes
Which equation below would produce the

following graph?
A) f(x)=-(x + 1)(x - 1)(x - 5)
B) S(x) - (x + 4)(x - 1)(x - 5)
C) f(x) - (x - 1)(x + 1)(x + 5)
D) S() --(x - 1)(x + 1)(x + 5)

Which equation below would produce the following graph? A) f(x)=-(x + 1)(x - 1)(x-example-1
User Charlie
by
5.4k points

1 Answer

2 votes
I’ve never solved a problem like this. But the first thing I would do is find the x and y intercepts. Make x = 0 and y = 0. You have to do this for each equation.

First function: -(0+1)(0-1)(0-5) = -5
The graph does seem to intercept at -5, but lets check the x intercept now when y = 0. X would equal -1, 1, and 5. The graph doesn’t hit 0 at all those points, so A is wrong

Second function: -(0+4)(0-1)(0-5) = -20
We can see right off the bat that the graph doesn’t intercept at y = -20

Third function: -(0-1)(0+1)(0+5) = 5
Again, the y intercept is -5, so we know this is wrong.

Fourth function: -(0-1)(0+1)(0+5) = 5
This is also incorrect. Maybe you wrote the question wrong, but none of these functions work
User Wrm
by
6.0k points